(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The aim of this study is to formulate the capecitabine loaded nanospheres of polycaprolactone-chitosan, cross linked with Tripolyphosphate for anticancer therapy, in order to enhance the bioavailability and to reduce the dose frequency. Formulations of capecitabine loaded nanospheres were prepared by double emulsion solvent evaporation and solvent diffusion methods. Fourier transmission infrared spectroscopy studies indicated no chemical interaction between drug and polymer. Scanning electron microscopy showed nanospheres having a discrete spherial structure without aggregation. The average particle size was found as 616 ± 110 to 713 ± 115 nm. In vitro release studies were performed by the dialysis membrane method. All the drug loaded batches were follwed zero order and sustained drug release over a period of 24 hrs. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22309 Bangladesh Pharmaceutical Journal 17(1): 18-24, 2014